Inconclusive results of slow cortical potential neurofeedback for the treatment of chronic post-stroke attention deficits - Sonja C. Kleih; Loic Botrel (Frontiers in Human Neuroscience, 2024)
IntroductionIndividuals who have suffered a stroke may experience long-lasting cognitive impairments that can worsen if left untreated. We investigated whether voluntary control of slow cortical potentials (SCP) through neurofeedback would help alleviate chronic post-stroke symptoms of impaired attention.MethodsThe study initially enrolled twenty-eight participants, but due to a high drop-out rate, only sixteen participants completed eight SCP neurofeedback training sessions within three to four weeks. During these sessions, we gave feedback to the participants on their ability to regulate SCPs on a computer screen.ResultsOur findings showed a non-significant increase in SCP regulation towards cortical negativity. On the behavioral level, we found improved test values in the divided attention and attentional flexibility subtests of the test battery for attention performance. However, we cannot eliminate the possibility that nonspecific effects influenced or caused our results. We have not observed any improvement regarding the effects of attention deficits on participants’ daily lives. We identified five individuals who could gain SCP control successfully and consistently towards negativity. In this group of responders, we observed an improvement in the test results related to divided attention but no other attention-related improvements.DiscussionBased on our observations, results of SCP neurofeedback training for the treatment of attention deficits after a stroke are inconclusive. More research is necessary to determine the effectiveness of SCP neurofeedback in helping stroke survivors cope with attention-related challenges in their daily lives.